Efficacy of Prednisone in Children with Acute Nonspecific Mesenteric Lymphadenitis: A Pilot Study - Momcilo Pavlovic; Zeljko Rokvic; Karolina Berenji (Acta Medica, 2022)
Background: Acute nonspecific mesenteric lymphadenitis (ANML) is a common cause of acute abdominal pain in children with no specific treatment. Methods: A total of 13 patients (6 boys, 7 girls) aged 7.3 (5–13.5) years with severe acute abdominal pain were evaluated using ultrasonography and laboratory tests to establish the diagnosis of ANML. They were treated with prednisone 1 mg/kg (max 40 mg daily) for a maximum of 5 days. The intensity of abdominal pain was evaluated before and after treatment using a numeric rating scale. Results: All patients had pain scores above 6/10 before, and below 4/10 after treatment with prednisone. Intensity of abdominal pain after treatment for 1–5 days decreased significantly (p < 0.001), with no recurrence at follow-up within 3 months. All other pre-existing signs and symptoms, such as nausea, vomiting, anorexia, fever, diarrhea, and constipation were found to disappear with no adverse effects of corticosteroid therapy. Conclusion: These results suggest that the treatment with prednisone in selective patients with ANML can reduce the duration of abdominal pain.